Recovery and Reduction of Non-Performing Loans – Podgorica Approach - Stijepović Ristan (Journal of Central Banking Theory and Practice, 2014)
Loan portfolio of Montenegro’s banking sector was largely affected by the growth in past due loans during the current financial crisis. High level of these loans limits banks’ lending activity which results in a decline in credit supply. Negative effects of the non-performing loans’ growth reflected adversely on economic strength of the real and households sectors. Majority of Montenegrin companies have significant liquidity problems and their defaults affect adversely the sound part of the economy, while reduced households spending reflects negatively on aggregate demand.